2000
DOI: 10.1002/etc.5620190610
|View full text |Cite
|
Sign up to set email alerts
|

Riverine endosulfan concentrations in the Namoi River, Australia: Link to cotton field runoff and macroinvertebrate population densities

Abstract: Abstract-Population densities of six dominant macroinvertebrate taxa (mayfly nymphs Jappa kutera, Atalophlebia sp., Tasmanocoenis sp., Baetis sp. and the caddisfly larvae Cheumatopsyche sp. and Ecnomus sp.) were negatively correlated to total endosulfan concentrations in the Namoi River (New South Wales, Australia) in the 1995/96 and 1997/98 cotton growing seasons (NovemberMarch). Total endosulfan concentrations measured in solvent-filled polyethylene bags (passive samplers) at the exposed sites correlated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
64
0
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(72 citation statements)
references
References 35 publications
2
64
0
1
Order By: Relevance
“…Entry routes of pesticides into adjacent bodies of water resulting from normal agricultural usage include spray drift, runoff, and leaching (e.g., Ganzelmeier et al, 1995;Capri and Trevisan, 1998; Van de Zande et al, 2000). Programmes and studies focusing on the detection of pesticides in an aquatic environment report traces of these toxicants in various bodies of water (Wan, 1989;Thoma and Nicolson, 1989;Frank et al, 1990;Teunissen-Ordelman and Schrap, 1996;Lahr and Banister, 1997;Liess and Schulz, 1999;Leonard et al, 2000). Hence, it is demonstrated that nontarget species living in water catchments of agricultural areas are potentially at risk when they have similar toxicant receptors as the target organisms.…”
Section: Introductionmentioning
confidence: 99%
“…Entry routes of pesticides into adjacent bodies of water resulting from normal agricultural usage include spray drift, runoff, and leaching (e.g., Ganzelmeier et al, 1995;Capri and Trevisan, 1998; Van de Zande et al, 2000). Programmes and studies focusing on the detection of pesticides in an aquatic environment report traces of these toxicants in various bodies of water (Wan, 1989;Thoma and Nicolson, 1989;Frank et al, 1990;Teunissen-Ordelman and Schrap, 1996;Lahr and Banister, 1997;Liess and Schulz, 1999;Leonard et al, 2000). Hence, it is demonstrated that nontarget species living in water catchments of agricultural areas are potentially at risk when they have similar toxicant receptors as the target organisms.…”
Section: Introductionmentioning
confidence: 99%
“…One disadvantage of the TRIMPS has been release of the solvent to the surrounding water. This problem may be largely avoided by using a protective nylonmesh bag to surround the passive samplers [10]. The lower surface area to volume ratio of TRIMPS leads to less susceptibility to saturation and depuration of sorbed compounds in comparison to SPMDs when in clean water.…”
Section: Introductionmentioning
confidence: 99%
“…The release of trimethylpentane may also be limited by movement through the aqueous boundary layer in the other direction [8]. Temperature changes measured in river water during the pesticide-spraying season [10] are likely to be less influential on the uptake of pesticide contaminants into the TRIMPS [16,17]. The influence of changes in the sorptive properties of particulates and dissolved organic matter in the water column is only likely to be important for the more hydrophobic compounds [18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the main factors affecting colonisation of benthic macroinvertebrates is substratum interaction with current velocity which results in great mobility in the substratum, generating an unstable habitat for benthic macroinvertebrates to settle in the GSM [22]. Another factor could be that excessive runoff that causes erosion on the catchment changes the abiotic condition of the benthos particularly increasing nutrients [23] and sediment loads [24]. Erosion of the un-vegetated catchment along the Vuvu River could be one of the main reasons for the occurrence of decreased number of benthic macroinvertebrate families on the GSM.…”
Section: Sources Of Variation Ssmentioning
confidence: 99%